MODAL SOSIAL : Komunitas Penjual Ikan Tui-Tuing Desa Mosso Majene - Ahmad Al Yakin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2012)
The purpose of this study was to determine the general idea of community – Tui-Tuing fishmonger and how community social capital Tui-Tuing fishmonger on the beach Labuang . The study was conducted in the village of Mosso Sendana Majene districts, the majority of income as fishermen and fish sellers Tui-Tuing. The targeted data retrieval are people who work as a fishmonger Tui-Tuing. The data taken in this study is qualitative. Data were collected by in-depth interviews and observation. The results showed that as a community that sells traditional food Mandar : tui - wink tapa (smoked flying fish) and Best Japanese , and became one of livelihood in the village of the District somba Sendana Majene . The job they have done for a long time to still be in progress until today. Some elements of social capital are found in Fish Seller Tui-Tuing, including participation (participation), values and social norms (social value and norms), and trust (mutual trust). It is based on the socio-cultural and economic conditions that describe the social activities that tend to be engaged in the sale of fish Tui-Tuing.